2021
DOI: 10.3390/su131910968
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of the Three-Year Action Plan to Fight Air Pollution on Air Quality and Associated Health Benefits in Sichuan Basin, China

Abstract: To continuously improve air quality, after implementation of the “Clean Air Action Plan, 2013–2017” (CAAP), the “Three-year Action Plan to Fight Air Pollution” (TYP) was further conducted from 2018 to 2020. However, the effectiveness of the TYP remains unclear in one of the major city-clusters of China, the Sichuan Basin. In this study, the bottom-up method was used to quantify the emission reduction during TYP based on the emissions inventory in Sichuan Basin in 2017 and the air pollution control measures ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The RMSE statistical values range from approximately 0 µg/m 3 to 50 µg/m 3 . Notably, the bias statistical values for NO 2 and CO are around ±6 µg/m 3 , indicating a high level of trustworthiness in the simulated values [47]. However, the bias statistical values for SO 2 and O 3 in January and April are relatively unstable.…”
Section: Model Verificationmentioning
confidence: 88%
See 2 more Smart Citations
“…The RMSE statistical values range from approximately 0 µg/m 3 to 50 µg/m 3 . Notably, the bias statistical values for NO 2 and CO are around ±6 µg/m 3 , indicating a high level of trustworthiness in the simulated values [47]. However, the bias statistical values for SO 2 and O 3 in January and April are relatively unstable.…”
Section: Model Verificationmentioning
confidence: 88%
“…In this study, we compared the air pollutant concentrations measured at typical air quality monitoring stations in Yibin City in 2021 with the corresponding hourly average pollutant concentrations simulated by the CMAQ model to verify the reliability of the modeling results (Table 2). The statistical indices used include root-mean-square error (RMSE) and bias [43][44][45][46][47]. The RMSE statistical values range from approximately 0 µg/m 3 to 50 µg/m 3 .…”
Section: Model Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…With the great efforts on air quality improvement in China via a series of national actions since 2013, for example, the Air Pollution Prevention and Control Action Plan (2013–2017) and the Three‐Year Action Plan to Fight Air Pollution (2018–2021), numerous reports with long‐term data sets have shown that PM 2.5 pollution has been effectively mitigated, with the national annual average PM 2.5 concentration dropping to 33 μg m −3 in 2020, but O 3 pollution presented a rapidly rising and spreading trend (J. Chen et al., 2021; S. Chen et al., 2020; Feng et al., 2019; Geng et al., 2019; Jiang et al., 2021). Previously only a few assessments of long‐term NO 3 radical have been performed, however, the use of high‐performance machine learning models provides the opportunity to estimate the long‐term NO 3 mixing ratio variability.…”
Section: Introductionmentioning
confidence: 99%